2018
DOI: 10.1136/gutjnl-2018-316221
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol inhibits T-cell glucose metabolism and hepatitis in ALDH2-deficient mice and humans: roles of acetaldehyde and glucocorticoids

Abstract: ALDH2 deficiency is associated with elevated acetaldehyde and glucocorticoids post-alcohol consumption, thereby inhibiting T-cell activation and hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 53 publications
2
59
0
1
Order By: Relevance
“…Acetaldehyde, which is a major by-product of ethanol, is one of the predominant compounds that are highly toxic to hepatocytes. ALDH2 is a key enzyme for acetaldehyde detoxification in the liver [45]. Moreover, ALDH2 deficiency is associated with increased acetaldehyde and glucocorticoids after alcohol consumption [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetaldehyde, which is a major by-product of ethanol, is one of the predominant compounds that are highly toxic to hepatocytes. ALDH2 is a key enzyme for acetaldehyde detoxification in the liver [45]. Moreover, ALDH2 deficiency is associated with increased acetaldehyde and glucocorticoids after alcohol consumption [45].…”
Section: Discussionmentioning
confidence: 99%
“…ALDH2 is a key enzyme for acetaldehyde detoxification in the liver [45]. Moreover, ALDH2 deficiency is associated with increased acetaldehyde and glucocorticoids after alcohol consumption [45]. We measured ADH1 and ALDH2 expression in mouse livers while using qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…21 Th17 cells not only promote liver inflammation and fibrosis in ALD by producing IL-17, 22 but may also help in liver repair by stimulating IL-22 production. 23 Although activated T cells are often detected in ALD and may contribute to disease pathogenesis, excessive alcohol drinking also caused broad immunosuppression 24 including inhibition of T cells via acetaldehyde and glucocorticoids, 25 thereby resulting in an increased risk of bacterial infection in patients with ALD.…”
Section: Key Pointsmentioning
confidence: 99%
“…The major difficulty is a lack of valid models in which a liver can support viral infection and alcohol metabolism that resembles liver injury caused by alcohol consumption and viral infection in alcoholic patients with chronic hepatitis C [41]. Our previous work demonstrated that alcohol-fed Aldh2 -/mice were less sensitive to concanavalin A-induced T-cell hepatitis than wild-type mice [42]. Further studies suggest that acetaldehyde directly suppresses cytokine production in T cells through the inhibition of aerobic glycolysis or stimulation of corticosterone release, which contributes to the occurrence of suppressed T-cell hepatitis in ethanol-fed Aldh2 -/mice [42].…”
Section: Aldh and Viral Liver Diseasesmentioning
confidence: 99%
“…Our previous work demonstrated that alcohol-fed Aldh2 -/mice were less sensitive to concanavalin A-induced T-cell hepatitis than wild-type mice [42]. Further studies suggest that acetaldehyde directly suppresses cytokine production in T cells through the inhibition of aerobic glycolysis or stimulation of corticosterone release, which contributes to the occurrence of suppressed T-cell hepatitis in ethanol-fed Aldh2 -/mice [42]. Cho et al suggested that the ADH/ALDH pathway also exerts a potent antiviral activity, likely mediated through the catalysis of retinol (ROL) and RA biogenesis, leading to the expression of interferon-stimulated genes (ISGs) [38].…”
Section: Aldh and Viral Liver Diseasesmentioning
confidence: 99%